Neuroinflammation, oxidative stress, and blood-brain barrier (BBB) disruption in acute Utah electrode array implants and the effect of deferoxamine as an iron chelator on acute foreign body response - Bennett, Cassie (Biomaterials, 2018)
The use of intracortical microelectrode arrays has gained significant attention in being able to help restore function in paralysis patients and study the brain in various neurological disorders. Electrode implantation in the cortex causes vasculature or blood-brain barrier (BBB) disruption and thus elicits a foreign body response (FBR) that results in chronic inflammation and may lead to poor electrode performance. In this study, a comprehensive insight into the acute molecular mechanisms occurring at the Utah electrode array-tissue interface is provided to understand the oxidative stress, neuroinflammation, and neurovascular unit (astrocytes, pericytes, and endothelial cells) disruption that occurs following microelectrode implantation. Quantitative real time polymerase chain reaction (qRT-PCR) was used to quantify the gene expression at acute time-points of 48-hr, 72-hr, and 7-days for factors mediating oxidative stress, inflammation, and BBB disruption in rats implanted with a non-functional 4×4 Utah array in the somatosensory cortex. During vascular disruption, free iron released into the brain parenchyma can exacerbate the FBR, leading to oxidative stress and thus further contributing to BBB degradation. To reduce the free iron released into the brain tissue, the effects of an iron chelator, deferoxamine mesylate (DFX), was also evaluated.